On commercial Н⁻ cyclotrons up to 30 MeV energy range for production of medicine isotopes - Papash, A.; Alenitsky, Y. (Вопросы атомной науки и техники, 2008)
A compact isochronous cyclotrons to accelerate negative hydrogen ions up to 30 MeV are widely used for production of medical isotopes and other applications. The physical and technical parameters of accelerators are compared. Measures to improve performance and to increase beam intensity are proposed.